HUBUNGAN ANTARA SOSIAL BUDAYA PADA MASYARAKAT DENGAN PERILAKU PEMBERIAN ASI EKSKLUSIF : SYSTEMATIC REVIEW - Ari Pratiwi; Mateus Sakundarno Adi; Ari Udijono; Martini Martini (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
ABSTRACTGlobally, the rates of exclusive breastfeeding remain lower than what is required to protect the health of women and children. Only 41% of infants under six months of age are exclusively breastfed. Mother’s attitudes toward providing exclusive breastfeeding can be influenced by various factors including social culture. The objective of this review is to summarize the evidence of an association between social culture with exclusive breastfeeding practices. A systematic search of Portal Garuda databases from January 2010 to November 2020 is conducted for cross-sectional studies regarding social culture as an influencing factor to exclusive breastfeeding practices. A narrative synthesis is used in this review according to the STROBE statement. Eight articles were eligible for this review. Social culture consistently correlated with exclusive breastfeeding practices. Midwives, physicians, and health workers need to educate pregnant women about the importance of exclusive breastfeeding to support the success of exclusive breastfeeding by mothers.